Ultrasound and microwave assisted extraction of acorn oil (Quercus brantii): Optimization and characterization - Samaneh Niari; Nasser Hamdami; Mohsen Dalvi-Isfahan; Alain Le-Bail (Applied Food Research)
This study aimed to optimize the extraction parameters and increase the oil yield, by comparing both microwave-assisted extraction (MAE) and ultrasound-assisted extraction (UAE) methods of extracting acorn oil (Quercus brantii). The study demonstrates that UAE and MAE are efficient, rapid, and resource-saving techniques for extracting acorn oil compared to conventional methods like Soxhlet extraction and long-duration maceration. UAE achieved a significantly higher oil yield (7.44 %) than MAE (5.45 %), reducing the extraction time from hours to just 33 min, and lowering solvent consumption. This efficiency makes UAE particularly advantageous for industrial-scale operations seeking to minimize environmental impact and operational costs. The findings further emphasize that UAE not only provides superior oil yield but also enhances the total phenolic content of the extracted oil, achieving a value 2.5 times higher than that obtained with MAE. Moreover, UAE demonstrated no significant increase in free fatty acids (FFA), maintaining the oil's quality, while MAE conditions showed a negative effect by increasing FFA levels. In addition to yield and quality, UAE also produced oil with superior color parameters, which could enhance consumer acceptability. These results underscore UAE's potential as a sustainable alternative, capable of reducing the environmental footprint by minimizing energy use, extraction time, and solvent waste.